6(x-3)+10=4x+4

Simple and best practice solution for 6(x-3)+10=4x+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(x-3)+10=4x+4 equation:


Simplifying
6(x + -3) + 10 = 4x + 4

Reorder the terms:
6(-3 + x) + 10 = 4x + 4
(-3 * 6 + x * 6) + 10 = 4x + 4
(-18 + 6x) + 10 = 4x + 4

Reorder the terms:
-18 + 10 + 6x = 4x + 4

Combine like terms: -18 + 10 = -8
-8 + 6x = 4x + 4

Reorder the terms:
-8 + 6x = 4 + 4x

Solving
-8 + 6x = 4 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-8 + 6x + -4x = 4 + 4x + -4x

Combine like terms: 6x + -4x = 2x
-8 + 2x = 4 + 4x + -4x

Combine like terms: 4x + -4x = 0
-8 + 2x = 4 + 0
-8 + 2x = 4

Add '8' to each side of the equation.
-8 + 8 + 2x = 4 + 8

Combine like terms: -8 + 8 = 0
0 + 2x = 4 + 8
2x = 4 + 8

Combine like terms: 4 + 8 = 12
2x = 12

Divide each side by '2'.
x = 6

Simplifying
x = 6

See similar equations:

| x=3/(4y-1) | | 6+10k=56 | | (-t/3)^2 | | .817= | | -c/-5=-12 | | 2x^2-25=5x | | 15mn(-4m+6mn-10n)= | | -r/2=13 | | -0.3(0.7x-0.9)=-1.89 | | y/2-9/5=9x-8/3 | | T/-4=-20 | | 50-5T=15 | | 7x+40=16 | | -2/3w=6 | | -5(x-3)-(2x+7)= | | y=lx+3l-1 | | 3/16x4/9 | | 24+2x=3x+48 | | (X+7)-8=12 | | 2e^3x=30 | | 24x+2x=3x+48 | | 30X+60-30X=60 | | 30X+30-30X=60 | | X2=36/64 | | 6(7-5x)-5x=252 | | 6x-14=6x+14 | | 11=s/2 | | 4x^3+12x^2+6x-2=0 | | 5=d/8 | | 0.1666666= | | (2n+6)4=-2n+4 | | =X/2*2× |

Equations solver categories